Prenatal Maternal Stress Predicts Childhood Asthma in Girls: Project Ice Storm. (8th May 2014) - Turcotte-Tremblay, Anne-Marie; Lim, Robert; Laplante, David P.; Kobzik, Lester; Brunet, Alain; King, Suzanne
Abstract : Little is known about how prenatal maternal stress (PNMS) influences risks of asthma in humans. In this small study, we sought to determine whether disaster-related PNMS would predict asthma risk in children. In June 1998, we assessed severity of objective hardship and subjective distress in women pregnant during the January 1998 Quebec Ice Storm. Lifetime asthma symptoms, diagnoses, and corticosteroid utilization were assessed when the children were 12 years old (N = 68 ). No effects of objective hardship or timing of the exposure were found. However, we found that, in girls only, higher levels of prenatal maternal subjective distress predicted greater lifetime risk of wheezing (O R = 1.11 ; 90% CI = 1.01–1.23), doctor-diagnosed asthma (O R = 1.09 ; 90% CI = 1.00–1.19), and lifetime utilization of corticosteroids (O R = 1.12 ; 90% CI = 1.01–1.25). Other perinatal and current maternal life events were also associated with asthma outcomes. Findings suggest that stress during pregnancy opens a window for fetal programming of immune functioning. A sex-based approach may be useful to examine how prenatal and postnatal environments combine to program the immune system. This small study needs to be replicated with a larger, more representative sample.